Unlocking Antibacterial Potential: Thiophene-2-carbaldehyde Modification of Acertannin from African Leaves as MurA Enzyme Inhibitors - Ilham Kurniawan; Nabilla Suhasfi Winarno (Universitas Pahlawan Tuanku Tambusai, 2025)
The global rise of antimicrobial resistance underscores the need for novel inhibitors targeting essential bacterial enzymes such as UDP-N-acetylglucosamine enolpyruvyl transferase (MurA). This study evaluates the antibacterial potential of three natural polyphenols—Acertannin from African leaves and structurally modified with Thiophene-2-carbaldehyde (TC) to enhance MurA inhibition. A validated QSAR model, incorporating hydrophobic, electronic, and steric descriptors, predicted significantly lower EC₅₀ values for TC-modified compounds, with TC-acertannin showing the highest predicted potency (EC₅₀ = 0.382 µM). Molecular docking revealed strong binding affinity to MurA, with ΔG = −7.8 kcal/mol and Ki = 1.88 µM, involving key interactions such as hydrogen bonding, π-anion, and π-sulfur contacts with residues CYS115, ARG120, ASN23, ARG91, LYS22 and GLU188. PASS prediction further indicated enhanced antibacterial activity and membrane-related mechanisms, with TC-Acertannin showing a Pa of 0.923 for membrane integrity agonism. These results highlight TC-modified tannin as promising MurA-targeted antibacterial agents and support the rational design of natural product-based inhibitors to combat antibiotic-resistant bacteria